DEFENSE MECHANISM OF AILEEN IN MONSTER MOVIE (2008) DIRECTED BY PATTY JENKINS’: A PSYCHOANALYTIC APPROACH - SETIYAWATI, FENNY ERNA (2011)
The research is proposed to analyze a defense mechanism in a film with the title Monster with Psychoanalytic Approach. There are two objectives: the first is to analyze the film in term of structural elements, and the second is to analyze the film based on Psychoanalytic Approach. This study is a descriptive qualitative study, using the film of Patty Jenkins’ Monster as the object of analysis. There are two kinds of data sources used in this analysis, namely primary and secondary. The primary data are the film and script of the film itself and the secondary data sources are books, internet and articles related to the subject. The technique of data collection in this research is library research by summarizing, paraphrasing and documenting the data. In analyzing the data, the writer employs descriptive qualitative analysis. The analysis is started by analyzing Aileen’s id, ego, superego, and then her anxiety. For the last, the writer makes an analysis of Aileen’s character using defense mechanism. The outcome of the study shows that the film illustrates defense mechanism of Aileen in a hard world in the early twentieth century. She worked as a prostitute and then she had to kill her client who hurt her as the defense to protect herself from that cruel man. Finally, the conclusion of this analysis is that the woman who is acknowledged as a weak creature can do anything to protect herself.